The Correlation of Organizational Role Stressors with Stress Level of ICU Nurses - Nursalam Nursalam; Ferry Efendi; Ni Luh Putu Dewi Puspawati (Universitas Airlangga, 2009)
Introduction : Work stress which is often experienced by ICU nurses may affects nurse’s performance, nurse’s health and wealth so that the factors which may affect work stress such as organizational role stressors must be noticed. This study was aimed to explain the correlation between organizational role stressors and work stress level in ICU Nurses.Methods : This study used cross-sectional design involved 13 respondents, taken by purposive sampling. The independent variable was organizational role stressors and the dependent variable was work stress. Data were collected by using questionnaires and analyzed using Spearman’s rho with level of significance α ≤ 0.05.Results : Results showed that there was no significant correlation between organizational role stressors and work stress level in ICU nurses with significance value p ≤ 0.139.Conclusion :It can be concluded that the organizational role stressors had no correlation with work stress level because there are so many factors that may affect work stress in ICU nurses. Discussion : Role overload however was experienced by ICU nurses as a mild stressors. This indicates the importance of increasing nurse’s quality and quantity by training and recruiting new nursing staffs.